2018
DOI: 10.1080/24701394.2018.1484116
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a duplicated mitochondrial region in Audubon’s shearwater based on MinION sequencing

Abstract: Mitochondrial genetic markers have been extensively used to study the phylogenetics and phylogeography of many birds, including seabirds of the order Procellariiformes. Evidence suggests that part of the mitochondrial genome of Procellariiformes, especially albatrosses, is duplicated, but no DNA fragment covering the entire duplication has been sequenced. We sequenced the complete mitochondrial genome of a non-albatross species of Procellariiformes, Puffinus lherminieri (Audubon's shearwater) using the long-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 52 publications
(58 reference statements)
6
15
0
Order By: Relevance
“…Contamination in the field was also unlikely since new sampling supplies were used for every sample. Given that only 10% of the cytb sequences presented such ambiguities (which may be due to heteroplasmy; Torres et al, 2018), we removed such sequences for further analyses. However, for the CR, since a third of the total sequences were involved, we kept all CR data in further analyses, considering two haplotype phases for MrBayes and *BEAST analyses (although we recognize that these data are in violation of the assumption that sequences to be phased are under Hardy–Weinberg equilibrium; see discussion below).…”
Section: Resultsmentioning
confidence: 99%
“…Contamination in the field was also unlikely since new sampling supplies were used for every sample. Given that only 10% of the cytb sequences presented such ambiguities (which may be due to heteroplasmy; Torres et al, 2018), we removed such sequences for further analyses. However, for the CR, since a third of the total sequences were involved, we kept all CR data in further analyses, considering two haplotype phases for MrBayes and *BEAST analyses (although we recognize that these data are in violation of the assumption that sequences to be phased are under Hardy–Weinberg equilibrium; see discussion below).…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial genome of several Procellariiformes presents tandem repeats (Abbott et al 2005;Lounsberry et al 2015), including P. lherminieri (Torres et al 2018). In this taxon, a duplicated region comprising two copies of the CR was found, yielding the presence of double peaks on chromatograms.…”
Section: Sequencing Artifacts Due To Mtdna Duplication and Uncertainties About Molecular Clock Ratesmentioning
confidence: 96%
“…Additionally, it is important to note that data analyses to generate mitochondrial genomes (via genome skimming) exclusively using ONT data are not entirely a straightforward process. Other studies have shown complete mtDNA assemblies combining ONT datasets and high‐throughput short‐read datasets from Illumina to improve overall consensus quality (Chandler et al, 2017; Torres et al, 2018). For instance, the complete mitogenome assembly of a clinical‐interest nematode, Nippostrogylus brasiliensis , was improved using dual datasets (Chandler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The cost–benefit and accessibility of ONT allow obtaining genome‐wide and organellar DNA sequences in situ without the need (and avoid the associated problems) of PCR‐based amplification. Previous efforts have been made to obtain mitochondrial genomes using ONT sequencing data, but to overcome the read noisiness and improve assembly quality, short‐read data from Illumina platform were also included (Chandler et al, 2017; Torres et al, 2018). Herein, we propose that with enough mitochondrial DNA coverage (genome skimming), the mitogenome could be accurately reconstructed using ONT‐only data combining several computational assembly routines to solve known issues and error‐prone sites in the sequence.…”
Section: Introductionmentioning
confidence: 99%